Indonesia Tourism, Socio Renewable Energy, Socio Economic and Socio Tourism Research Trend - Halim, Paisal; Badruddin, Syamsiah; Setiawan, Muhammad Ikhsan; Zulkifli, Che Zalina (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Indonesia became one of the strongest economies in Asia Pacific. Sustainable tourism is crucial for Indonesia due to the country's rich biodiversity, diverse cultures, and reliance on tourism as a significant economic driver. Sustainable tourism in Indonesia refers to the practice of promoting tourism activities that minimize negative impacts on the environment, respect and preserve local cultures, and contribute to the well-being of local communities. Indonesia, with its rich biodiversity, cultural diversity, and natural beauty, recognizes the importance of sustainable tourism to ensure the long-term viability of its tourism industry and the preservation of its natural and cultural assets. Renewable energy tourism, also known as green or sustainable energy tourism, is gaining importance globally as countries seek to promote environmental sustainability and address climate change. By integrating sustainability into tourism practices, Indonesia ensures the long-term viability of its tourism industry. This approach helps balance economic growth with environmental and social considerations, preventing negative consequences that could harm the industry in the future. SCOPUS analyze search results, Social Renewable Energy, Social Economic and Social Tourism 7236 documents result since 1981 to 2023, all field article. Promising in research and publication for Social Renewable Energy, Social Economic and Social Tourism. Compare top 15 affiliations, dominant affiliations from China. Still no Indonesia research institution in top 15 of the list. Compare top 15 countries, the best 3 countries are China, USA and UK. In ASIA and ASEAN, Indonesia under China, Pakistan, India, Iran and Malaysia. This is real challenge for Indonesia research institution to expand their research in Social Renewable Energy, Social Economic and Social Tourism. Compare top 15 funding sponsors, dominant from China, ASEAN dominant from Malaysian and Vietnam, there are no Indonesia funding sponsor.